(untitled) (Journal of the College of Education for Women, 2018)
The goal of current research to know the according of scientific values in the curriculum of chemistry sixth - grade science To achieve this goal wasa to build aalistaofa scientifica values toa be included in the curriculum of chemistry sixth - grade science after seeing a group of literature and previous studies, the list presented to a group of arbitrators and specialists in educational and psychological sciences and methods of teaching science, and curricula and teaching methods , Arbitrators and specialists have expressed their views and comments on the tool, and that the list was formed in final form (9) values Head of scientific includes ( 35) sub - value, then the researcher analyzed the chemistry curriculum for sixth grade Scientific and applied branches of biodegradation in the light of the list that has been built, and adopted the idea of both types (Explicit and implicit) as a unit for recording and repetition as a unit d prepare , and was sure of honesty and consistency, and the results showed that the chemistry curriculum for sixth grade Applied and scientific branches of biodegradation achieved (304) repeat as the branch of biological got (160) recurrence rate (52, 63%), and the branch of applied (144) recurrence rate (47.37%).